Molecular Localization of Latent Epstein – Barr Virus Early Repeats (EBERS) in Cervical Tissues with Adenocarcinoma by RNA-In Situ Hybridization - Mohammed Ali, Saad H. (Iraqi Journal of Cancer and Medical Genetics, 2015)
Epstein-Barr virus (EBV) has an etiological relevancy to the pathogenesis of an increasing number of cancers. Cervical carcinogenesis is a multifactorial stepwise process that has a possible link with many infective factors, including EBV infections where the standard procedures in their histopathological diagnosis rely on in situ hybridization. This retrospective research was designed to(1) investigate the frequency of EBV infections in correlation with the age of patients with cervical adenocarcinoma, (2)validate the impact this virus on the histopathological grade expression of those cancers; and(3)rating the EBV-infections by evaluating the signal scores and intensities of RNA -in situ hybridization (RISH) reactions. A total number of 49 patients, who had undergone hysterectomies or punch biopsies from their cervices were enrolled in this study. Twentyone tissues were collected from cervical adenocarcinoma where as the control groups comprised 28 blocks from cervical tissues either without any significant pathological changes or from chronic cervicitis. Molecular detection of Latent EpsteinBarr Virus Early Repeats (EBERS) was performed by using ultra-sensitive versions of RNA-in situ hybridization (RISH) technique. The mean age of this group of Iraqi patients with cervical adenocarcinoma was 46.7 ± 11.6 years and histopathologically, well and poor grades of cervical adenocarcinoma each constituted 14.3% whereas 71.4% was moderately differentiated. The EBV was detected in 38.1% (8 out of 21) of cervical adenocarcinoma tissues while EBERs were neither detected in chronic cervicitis tissues nor in those healthy cervical tissues. Seven out of eight cases (87.5%) with positive EBERs–ISH reactions have well and moderate differentiation grades while only one case (12.5%) has poor differentiation. It may conclude that EBV infections in cervical adenocarcinoma could point for an initiating and/or cofactor roles, along with other important oncogenic viruses, in cervical oncogenesis. The observed impact of EBV on the differentiation of cervical adenocarcinoma could possibly shade light on an early- eventual occurrence of such molecular attack in cervical carcinogenesis.